2021
DOI: 10.3390/nu13093043
|View full text |Cite
|
Sign up to set email alerts
|

The Pro-Health Benefits of Morusin Administration—An Update Review

Abstract: Prenylflavonoids are widespread in nature. Plants are valuable sources of natural polyphenolic compounds with isoprenyl groups, which include flavones, flavanones, chalcones and aurones. They can be found in flowers, bark and stems. One of the most important compounds found in the bark of white mulberry (Morus alba) is morusin, a prenylated flavone with interesting pro-health properties. The research carried out so far revealed that morusin has antioxidant, antitumor, anti-inflammatory and anti-allergic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Treatment of 21 and 22 with aqueous 60% KOH yielded two other important natural products, morusin ( 23 ) and cudraflavone B ( 24 ), respectively. Both 23 and 24 were previously reported from Morus alba and exhibited a broad spectrum of interesting biological activities. , …”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Treatment of 21 and 22 with aqueous 60% KOH yielded two other important natural products, morusin ( 23 ) and cudraflavone B ( 24 ), respectively. Both 23 and 24 were previously reported from Morus alba and exhibited a broad spectrum of interesting biological activities. , …”
mentioning
confidence: 81%
“…Both 23 and 24 were previously reported from Morus alba and exhibited a broad spectrum of interesting biological activities. 25,26 Due to the structural similarities between 23 and 24, distinction between the two natural compounds was a challenge and may lead to misassignment. Therefore, the structures of the regioisomers 23 and 24 were further confirmed by 2D NMR (HMBC and HMQC) data analysis.…”
mentioning
confidence: 99%
“…Our verified experiments in human L02 hepatocytes revealed that the expression levels of ADORA1 genes were upregulated in insulin resistance, while morusin treatment markedly increased cellular glucose consumption stimulated by insulin and downregulated ADORA1 expression. Morusin is a prenylated flavone that allows for versatile salutary effects, including antioxidant, antitumor, and anti-inflammatory activities ( Choi et al, 2020 ; Panek-Krzysko and Stompor-Goracy, 2021 ). Recently, the metabolically beneficial effects of morusin have been gradually recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolic compounds, which are commonly found in fruits, wine, and herbs, constitute a group of over 8000 substances. Among them we can find flavones and their hydroxylated analogues flavonols [ 1 , 2 ]. The health-promoting properties of flavonoids arise from their cyclic structures with conjugated double bonds, and from the presence of various functional groups in the aromatic rings.…”
Section: Introductionmentioning
confidence: 99%